Studies on the composition and energy of secondary cosmic rays with the Tragaldabas detector - Fontenla Barba, Yanis
Cosmic rays cover a wide range of scientific fields of research: study and development of particle detectors, study of very high energy particles, astroparticles and nuclear astrophysics. . This thesis, I summarize the work realized in the research and development of Trasgo detectors for identification of muons and electrons originated by cosmic rays, and for installation of detection systems and study of atmospheric showers with several arrays of detectors build at University of Santiago de Compostela (USC) and other geographic locations such as the Antartic continent. The results presented were electron-muon identification for Tragaldabas detector from simulations of EnsarRoot framework and, response of both Tragaldabas and Tristan, lateral distribution study and study of clusters at ground level made with simulations of Corsika program. These allow to identify the nature of the cosmic ray at ground level with Tragaldabas and characteristics of primary cosmic rays (mass, energy and arrival direction) with Trasgo-like detectors installed over vast areas at ground level of the USC.